2023
DOI: 10.3390/pathogens12060749
|View full text |Cite
|
Sign up to set email alerts
|

Serological Prevalence of Crimean–Congo Hemorrhagic Fever Virus Infection in Small Ruminants and Cattle in The Gambia

Abstract: Crimean–Congo hemorrhagic fever virus (CCHFV) is a widely distributed tickborne zoonotic agent that infects a variety of host species. There is a lack of information on the true geographic distribution of the prevalence and risk of CCHFV in West Africa. A countrywide cross-sectional study involving 1413 extensively managed indigenous small ruminants and cattle at livestock sales markets and in village herds, respectively, was carried out in The Gambia. In sheep, an overall anti-CCHFV antibody prevalence of 18.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Previous studies found a higher proportion of female than male wild boar infested by ticks, possibly caused by behavioral differences (37). Similarly, other studies have found a higher proportion of CCHFV-seropositive female cattle (38,39). However, statistically significant differences in CCHFV seropositivity between sexes had not previously been found in the limited serosurveys carried out in wild boar.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies found a higher proportion of female than male wild boar infested by ticks, possibly caused by behavioral differences (37). Similarly, other studies have found a higher proportion of CCHFV-seropositive female cattle (38,39). However, statistically significant differences in CCHFV seropositivity between sexes had not previously been found in the limited serosurveys carried out in wild boar.…”
Section: Discussionmentioning
confidence: 89%
“…CCHF is caused by the CCHF virus (CCHFV), a member of the genus Orthonairovirus and family Nairoviridae [ 7 ]. Human infections arise from tick bites or direct contact with infected animals or animal products and present with symptoms ranging from fever, headaches, nausea, and myalgia to severe systemic haemorrhagic fever, with a case fatality rate of up to 40% [ 8 ]. The virus circulates in an enzootic tick–vertebrate–tick cycle involving various domestic animals and wildlife.…”
Section: Introductionmentioning
confidence: 99%